Field Data from the West Area of Samos Archaeological Project (WASAP), 2021–2024 - Michael Loy; Katerina Argyraki; Anastasia Christophilopoulou; Georgia Delli; Matthew Evans; Sabine Huy; Alexandra Katevaini; Naoíse Mac Sweeney; Jana Mokrišová; Enrico Regazzoni; Anastasia Vasileiou (Journal of Open Archaeology Data, 2025)
The West Area of Samos Archaeological Project was an interdisciplinary fieldwork project, combining reconnaissance survey, intensive pedestrian fieldwalking, ethnographic research and drone photography in west Samos. It was co-directed by Anastasia Christophilopoulou (Cambridge/Boston MFA), Michael Loy (Cambridge/Durham), Naoíse Mac Sweeney (Vienna) and Jana Mokrišová (Cambridge, 2021 and 2022 only), under the aegis of the British School at Athens and the Hellenic Ministry of Culture. These data were collected using field methodologies well-practiced within the Aegean, using a common vocabulary and data structure to field projects of similar scope on neighbouring islands and mainlands.